Genetic polymorphism of ALDH2 linkage to kidney function status of East Nusa Tenggara alcohol drinkers and cigarette smokers - Busyra Busyra; Yudha Nurhantari; Suhartini Suhartini; Maria Agnes Etty Dedy; Tri Ratnaningsih (Journal of Community Empowerment for Health, 2021)
Chronic kidney disease is a preventable high-burden disease. Several risk factors for impaired kidney function have been identified, including lifestyles, such as alcohol drinking and cigarette smoking. However, the evidence remains inconsistent. East Nusa Tenggara has the largest proportion of heavy alcohol drinking among all provinces in Indonesia. Genetic polymorphism of aldehyde dehydrogenase 2 (ALDH2) is related to alcohol drinking behavior through the inactivity of the ALDH2 enzyme, which leads to toxic acetaldehyde accumulation. This study aims to recognize the linkage of ALDH2 genotypes to kidney function among alcohol drinkers and cigarette smokers in East Nusa Tenggara. This study was a cross-sectional study of East Nusa Tenggara ethnicity, aged 18-60 years old. Demographic and lifestyle data were obtained via a questionnaire. DNA analysis was conducted with the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) technique. Creatinine and BUN levels were measured with a chemistry analyzer. Afterward, the estimated glomerular filtration rate (eGFR) was calculated from creatinine value using the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation. The association between kidney function status and alcohol drinking and cigarette smoking habits were analyzed using the chi-square test, then stratified based on genotype groups. Fifty-one subjects were included in this study, while the mean age was 26.33±1.33 years and the median age was 22 years. There were 37 (72.5%) alcohol drinkers and 14 (27.5%) non-drinkers; 28 (54,9%) cigarette smokers and 23 (45.1%) non-smokers. This study revealed no significant association between kidney function status and alcohol drinking habits. Cigarette smoking habits were inversely associated with eGFR decline and creatinine elevation in wild-type ALDH2 groups.